2022
DOI: 10.1039/d1dt03296h
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the spatial distribution of copper sites on the selectivity of the oxygen reduction reaction

Abstract: Moving towards a hydrogen economy raises the demand for affordable and efficient catalysts for the oxygen reduction reaction. Cu-bmpa (bmpa = bis(2-picolyl)amine) is shown to have moderate activity, but poor...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 82 publications
(120 reference statements)
3
33
0
Order By: Relevance
“…In addition to the ORR, the catalytic activity of [Cu 2 L(μ-OH)] 3+ for the hydrogen peroxide reduction reaction (HPRR) is of interest because H 2 O 2 is found as a detectable intermediate in the aqueous electrochemical ORR mechanism of other copper complexes with tetradentate pyridylamine ligands that is formed after the two-electron reduction of oxygen. 36,39,41,53,54 In the presence of 1.1 mM H 2 O 2 , which is the same concentration as the maximum solubility of oxygen in PB, a catalytic wave was observed with a slightly earlier onset than the ORR (Figure 3b). As this earlier onset is only present in the first scan, we contribute this occurrence to the weak binding of H 2 O 2 to the oxidized form of the catalyst, although such a species could not be detected by other techniques like NMR.…”
Section: Cyclic Voltammetry Of [Cu 2 L(μ-oh)] 3+mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the ORR, the catalytic activity of [Cu 2 L(μ-OH)] 3+ for the hydrogen peroxide reduction reaction (HPRR) is of interest because H 2 O 2 is found as a detectable intermediate in the aqueous electrochemical ORR mechanism of other copper complexes with tetradentate pyridylamine ligands that is formed after the two-electron reduction of oxygen. 36,39,41,53,54 In the presence of 1.1 mM H 2 O 2 , which is the same concentration as the maximum solubility of oxygen in PB, a catalytic wave was observed with a slightly earlier onset than the ORR (Figure 3b). As this earlier onset is only present in the first scan, we contribute this occurrence to the weak binding of H 2 O 2 to the oxidized form of the catalyst, although such a species could not be detected by other techniques like NMR.…”
Section: Cyclic Voltammetry Of [Cu 2 L(μ-oh)] 3+mentioning
confidence: 99%
“…On the other hand, electrochemical studies that have reported the ORR activity of homogeneous metal complexes with two [36][37][38] or even three 37,39,40 copper atoms in aqueous solutions all lack evidence that direct cooperativity between the copper centers takes place during catalysis. The lack of cooperativity can be explained by the fact that covalently linking copper sites will not invariably result in synergy between the metal centers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The electronic structure and electrochemical characterization can be changed, which is beneficial for the ORR performance. [6][7][8] In recent years, covalent triazine frameworks (CTFs) have been utilized for a broad range of applications, including gas separation and storage, chemical sensing and catalysts, owing to their unique physicochemical properties. 9,10 In addition, most CTF materials have a porous structure, abundant heteroatomic sites and a large proportion of nitrogen species, which gives CTF materials potential for use as efficient ORR electrocatalysts.…”
Section: Introductionmentioning
confidence: 99%
“…The electronic structure and electrochemical characterization can be changed, which is beneficial for the ORR performance. 6–8…”
Section: Introductionmentioning
confidence: 99%